Minimal influence of future Arctic sea ice loss on North Atlantic jet stream morphology - Y. Anderson; J. Perez; A. C. Maycock (Weather and Climate Dynamics)
The response of the North Atlantic jet stream to Arctic sea ice loss has been a topic of substantial scientific debate. Some studies link declining Arctic sea ice to a weaker, wavier jet stream, which potentially increases the occurrence of extreme weather events. Other studies suggest no causal link between Arctic sea ice loss and the jet stream, instead attributing jet variations to internal variability. Current methods for characterising the low-level jet typically use zonal wind speeds averaged over the North Atlantic sector, which can result in the loss of important aspects of jet morphology. This study uses a new two-dimensional feature-based method to investigate the winter low-level jet response to future Arctic sea ice loss using idealised prescribed sea ice experiments from the Polar Amplification Model Intercomparison Project (PAMIP). In contrast to earlier studies that have focused on seasonal-average changes, this study also explores how daily jet variability is altered by sea ice loss. The results show a significant equatorward shift in mean jet latitude for three of the six PAMIP models analysed and a multi-model-mean equatorward jet shift of 0.6 ± 0.1°. Four of the six models show a significant weakening of the westerlies on the poleward side of the North Atlantic jet and a strengthening on the equatorward side. However, there is no change in jet speed and jet tilt across all models and no robust change in jet mass (area-weighted speed) when using the feature-based jet identification. Three of the six models show an increase in the frequency of split-jet days, but this does not strongly affect the overall distributions of daily jet latitude, speed and mass. Likewise, the results show no significant change in the daily variability in jet features, and changes in interannual variability are inconsistent between the models. The results extend previous studies characterising jet response from a zonally averaged perspective and suggest that it is unlikely that future Arctic sea ice loss will cause significant weakening of the North Atlantic jet stream or an increase in jet variability.